2016
DOI: 10.1111/afe.12159
|View full text |Cite
|
Sign up to set email alerts
|

Ant attendance of the cotton aphid is beneficial for okra plants: deciphering multitrophic interactions

Abstract: 1 Aphids are pest species of many crops and biocontrol methods are often ineffective. Ant-aphid associations can be mutualistic or antagonistic, with ants increasing or reducing aphid numbers. Within-species plant variation or other herbivores may further influence these ant-aphid interactions. 2 Okra is an economically important crop in Cameroon. Several okra varieties are grown here and attacked by the facultatively ant-tended cotton aphid Aphis gossypii. We conducted field and screenhouse experiments where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…However, ants are not always beneficial for aphids but can also act as predators (Billick, Hammer, Reithel, & Abbot, 2007;Singh, Zytynska, Hanna, & Weisser, 2016). In many aphid systems, both mutualistic ants and predators can be influenced by intraspecific variation in the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, ants are not always beneficial for aphids but can also act as predators (Billick, Hammer, Reithel, & Abbot, 2007;Singh, Zytynska, Hanna, & Weisser, 2016). In many aphid systems, both mutualistic ants and predators can be influenced by intraspecific variation in the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ants are not always beneficial to aphids, as recently shown by Singh et al . () examining aphid–ant associations ( Ap. gossypii Glover and Pheidole dea Santschi, respectively) on okra, Abelmoschus esculentus (L.) Moench (Malvales: Malvaceae) in the field and under controlled screenhouse conditions in the Cameroons, West Africa.…”
Section: Categories Of Specialismsmentioning
confidence: 99%
“…Singh et al . (, p. 270) reported that ‘In the field, ants did not protect aphids from their natural enemies and syrphid larvae reduced aphids by 42%. Additionally, aphid recruitment of ants reduced chewing herbivore damage by 11% and indirectly increased okra fruit set.…”
Section: Categories Of Specialismsmentioning
confidence: 99%
“…The cost to benefi t ratio in mutualism changes with the intrinsic features of both partners (e.g. the initial number of partners at the commencement of a relationship) and biotic/abiotic environmental factors (Stadler & Dixon, 1998;Styrsky & Eubanks, 2010;Yoo & Holway, 2011;Barton & Ives, 2014;Singh et al, 2016). Thus, mutualism has a context-dependent aspect, that is, the net benefi ts for a given species depend on ecological conditions (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%